General Budget to the Requirements of International Accounting and Applicability in Iraq - Miaad AbdUlkadhim Jard AL-kefari, Ahmed Rahi Abed, Ahmed Mahdi Hadi, (Opción, 2019)
This paper examines the difficulties and open doors for Iraq in changing from its national Unified Accounting System (UAS) to International Financial Reporting Standards. The examination utilized a subjective research approach counting two research techniques. For documented assets to the bookkeeping framework and the strain to change, the content examination was utilized. The results showed that the current circumstance in Iraq is a case of institutional isomorphism, explicitly coercive isomorphism by the World Bank and IMF; mimetic isomorphism by the IOCs and regularizing isomorphism by the Big 4 bookkeeping firms.